Analisis Kinerja Keuangan pada Pemerintah Kabupaten/Kota di Provinsi Jambi Tahun 2020-2022 - Sinaga, Jenita; Z, Rico Wijaya; Hernando, Riski (Universitas Batanghari Jambi, 2024)
This study aims to evaluate the financial performance of district/city governments in the province of Jambi during the period of 2020-2022, measured using the Degree of Decentralization Ratio, Local Financial Dependency Ratio, Local Financial Independence Ratio, Local Own Revenue Effectiveness Ratio, and Expenditure Efficiency Ratio. This research is a descriptive quantitative study that utilizes secondary data from audited Local Government Budget Realization Reports. The results show diverse patterns of financial performance: the majority of district/city governments have a Very Low Degree of Decentralization, Local Financial Independence tends to be Extremely Low with an instructive relationship pattern, Local Financial Dependency is generally high, Local Own Revenue Effectiveness is mostly Very Effective with diverse distributions, and Expenditure Efficiency is generally categorized as Efficient.